A Comprehensive Survey of Recent Internet Measurement Techniques for Cyber Security. Issue 128 (May 2023) - Safaei Pour, Morteza; Nader, Christelle; Friday, Kurt; Bou-Harb, Elias
Abstract: As the Internet has transformed into a critical infrastructure, society has become more vulnerable to its security flaws. Despite substantial efforts to address many of these vulnerabilities by industry, government, and academia, cyber security attacks continue to increase in intensity, diversity, and impact. Thus, it becomes intuitive to investigate the current cyber security threats, assess the extent to which corresponding defenses have been deployed, and evaluate the effectiveness of risk mitigation efforts. Addressing these issues in a sound manner requires large-scale empirical data to be collected and analyzed via numerous Internet measurement techniques. Although such measurements can generate comprehensive and reliable insights, doing so encompasses complex procedures involving the development of novel methodologies to ensure accuracy and completeness. Therefore, a systematic examination of recently developed Internet measurement approaches for cyber security must be conducted to enable thorough studies that employ several vantage points, correlate multiple data sources, and potentially leverage past successful techniques for more recent issues. Unfortunately, performing such an examination is challenging, as the literature is highly scattered. In large part, this is due to each research effort only focusing on a small portion of the many constituent parts of the Internet measurement domain. Moreover, to the best of our knowledge, no studies have offered an in-depth examination of this critical research domain in order to promote future advancements. To bridge these gaps, we explore all pertinent facets of utilizing Internet measurement techniques for cyber security, ranging from threats within specific application domains to threats themselves. We provide a taxonomy of cyber security-related Internet measurement studies across two dimensions. One dimension relates to the many vertical layers (and components) of the Internet ecosystem, while the other relates to internal normal functions vs. the negative impact of external parties in the Internet and physical world. A comprehensive comparison of the gathered studies is also offered in terms of measurement technique, scope, measurement size, vantage size, and the analysis approach that was leveraged. Finally, a discussion of the roadblocks to performing effective Internet measurements and possible future research directions is elaborated.